Sistema de evaluación del desempeño de 360º por competencias, como mecanismo para mejorar la calidad en las operaciones de empresas constructoras de la provincia de Pichincha - Espinoza Granda, William Rodrigo (2015)
This research "System of evaluation of the performance of 360° competency, as a mechanism to improve the quality of the operations of the Pichincha province construction companies." intends to propose a design of competency-based performance evaluation applied to the staff of the company Mendoza Pena, in order to determine the influence of the quality of the company's operations. For research, they worked with a sample of 61 companies, to be a large population of 594 companies considered to employ simple random sampling to quantify variables such as occurs in the market. Considered a confidence level of 90%, which is equivalent to 1.65 standard deviations, with a margin of error of 10% and 50% acceptance. Being a descriptive research were the first observations directly in the company under study, since the purpose of this is the evidence if the design of a system of evaluation by competences in construction companies will improve the quality of its operations and exploratory because it allows the characterization of the context of the construction companies, and to gather the information used data collection techniques such as surveys, to identify the causes and consequences in which are immersed such companies. After the findings determined that the system is going to propose is that of 360 ° competency assessment, based on the Likert scale, this, in order to make the evaluation results are a more complete and provide managers the current performance of staff and thus take the corrective measures necessary to improve the performance. Finally the conclusions based on the evidence that are taken into account to develop recommendations which are the result of the investigation.